PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PECAHAN KELAS V SD NEGERI 067092 MEDAN - Julia Safitri; Hasanah, Hasanah (Bajang Institute, 2024)
This research aims to describe and determine the improvement in student learning outcomes after applying the Discovery Learning Model to fraction material in class V elementary school. This research is Classroom Action Research (PTK) or classroom action research. This research was conducted at SD Negeri 097092 Medan. The subjects of this research were class V students at SDN 067092 Medan, consisting of 23 people. To collect data in this research, researchers used observation, provided test instruments and carried out documentation. The use of the Discovery Learnin model in mathematics learning about fractions in class V at SD 067092 Medan was carried out in 2 cycles. From the research results, it is known that in cycle I, of the 23 class V students at SD 067092 Medan, 10 students received an average score above the KKM. Meanwhile, 13 other students did not get a score above the KKM. In cycle II, out of 23 class V students, 20 students got an average score above the KKM. Only 3 students in class V at SD 067092 Medan, the other students did not get a score above the KKM. There was an increase in the learning outcomes of class V students at SD 067092 Medan by 34.86% in cycle I, namely from 26% at the time of observation to 60.86% at the end of cycle I. From the end of cycle II there was a significant increase in student learning outcomes, namely 60.95,%. From 26% at the time of observation to 86.95% at the end of cycle II. From these results it can be said that the Discovery Learning model can improve student learning outcomes in fraction material in class V elementary school